Highly Stable and Active Solid‐Solution‐Alloy Three‐Way Catalyst by Utilizing Configurational‐Entropy Effect. Issue 16 (10th March 2021) - Kusada, Kohei; Wu, Dongshuang; Nanba, Yusuke; Koyama, Michihisa; Yamamoto, Tomokazu; Tran, Xuan Quy; Toriyama, Takaaki; Matsumura, Syo; Ito, Ayano; Sato, Katsutoshi; Nagaoka, Katsutoshi; Seo, Okkyun; et al.
Abstract: Since 1970, people have been making every endeavor to reduce toxic emissions from automobiles. After the development of a three‐way catalyst (TWC) that concurrently converts three harmful gases, carbon monoxide (CO), hydrocarbons (HCs), and nitrogen oxides (NO x ), Rh became an essential element in automobile technology because only Rh works efficiently for catalytic NO x reduction. However, due to the sharp price spike in 2007, numerous efforts have been made to replace Rh in TWCs. Nevertheless, Rh remains irreplaceable, and now, the price of Rh is increasing significantly again. Here, it is demonstrated that PdRuM ternary solid‐solution alloy nanoparticles (NPs) exhibit highly durable and active TWC performance, which will result in a significant reduction in catalyst cost compared to Rh. This work provides insights into the design of highly durable and efficient functional alloy NPs, guiding how to best take advantage of the configurational entropy in addition to the mixing enthalpy. Abstract : PdRuIr ternary solid‐solution alloy nanoparticles exhibit highly durable and active three‐way catalyst performance. This work provides insights into the design of highly durable and efficient functional alloy catalysts, guiding how to best take advantage of the configurational entropy in addition to the mixing enthalpy.